Implementasi Pelayanan Samsat Corner dalam Rangka Meningkatkan Pelayanan Pajak Kendaraan Bermotor Tahun 2014 - Amri, Pahmi; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2015)
Along with the issuance of the Joint Regulation of Governor of Yogyakarta Special Region, Regional Police Chief ofYogyakarta Special Region, and Operational Director of PT. Jasa Raharja No.35 Year 2008 No:B/4820/XI/2008 andNo: SKEB/12/2008 about the program to improve SAMSATâs excellent service, SAMSAT Corner was established. Vehicletax is one of tax incomes which affects regional income. Therefore, it is necessary to optimize the tax revenue ofvehicle through various efforts. One of the ways is by improving the satisfaction of vehicle taxpayers by giving anoptimal service quality. Based on the explanation above, the researcher was eager to find out the implementation ofSAMSAT Corner service at Galleria Mall in order to improve vehicle tax in 2014. In this research about the implementationof SAMSAT Corner service, a mix method âquantitative and qualitative methods â was employed. Firstly, thedata were collected quantitatively using survey approach. Then, the data were collected qualitatively. Based onthe data analysis, the implementation of SAMSAT Corner service at Galleria Mall has run well, as its index value is 3.59or in good category. SAMSAT Corner service is also influenced by several factors, among others are communication,human resources, disposition, and bureaucracy structure. Their index is 3.76, thus it is in good category as well. Thefinding in this research shows that the internal organizer of service which is maximum cannot guarantee a goodservice, because the internal assessment shows better result than the external one. Based on the analysis, it can beconcluded that the implementation of SAMSAT Corner service at Galleria Mall has run well and it gives positive effectsto society (vehicle taxpayers).However, the regulation that rules the operation of SAMSAT Corner service at GalleriaMallis not optimal yet, so it is necessary to study it again in order to have a clear regulation about SAMSAT Cornerservice.